DYNAMICS OF LABOUR PRODUCTIVITY CHANGES IN AGRICULTURE AT THE REGIONAL LEVEL IN SELECTED EUROPEAN UNION COUNTRIES - Joanna Jaroszewska; Robert Pietrzykowski (Acta Scientiarum Polonorum. Oeconomia, 2018)
A comparison of the labour productivity disproportions in agriculture is usually carried out at the state level. Conducted research usually concerns the countries of the so-called old Union and newly admitted countries. As a result of analyses carried out in such a way such and the aggregation effect information about the actual scale of diversification at the regional level are lost. The paper proposes an analysis at the NUTS level 2 for selected European Union countries to show their internal differentiation in terms of labour productivity and changes taking place in the analysed period. It was also found that the distribution of labour productivity in agriculture in the regions should also be defined, which would require the use of more advanced statistical methods.